The Role and Importance of Physical Exercise on the Aggression Level of High School Students - D. Popescu; A.M. Cosma; A.M. Cosma; G.A. Cosma (Editura Universitatii Transilvania din Brasov, 2023)
Introduction. The phenomenon of bullying is increasingly widespread among students and at the national level, all kinds of techniques and activities are being tried to combat it. Methods. In the present study, we aimed to measure the level of aggression among secondary school students, who participated in a Physical Education and Sports Program, held over a period of 6 months, with a frequency of 8 times/month. A number of 36 students, at the secondary school level, aged between 11- 15 years, from the rural environment, from the South-West Region of Oltenia, all enrolled in the same school, took part in this experiment. As a tool, the Aggression Questionnaire (AQ) was applied, with 4 scales: Physical Aggression, Verbal Aggression, Anger, and Hostility. Aggression was measured both before and after participation in the sports training program. Results. The results indicated a lower level of aggression at the end of the program, compared to the level present in the students, before following the sports training. Conclusions. Thus, physical and sports education can be an optimal means of controlling aggression and a catalyst for it in positive aspects and behaviors.